Closing the revolving door : a qualitative analysis of recovered heroin and cocaine addicts' experience of recovery and abstinence. - Fraser, Robin (My University, 2010)
A now sizeable body of substance-abuse research has examined the factors that contribute to a relapse; however, less research has been conducted on identifying factors in patients who do not relapse. In South Africa, relatively limited qualitative research is available on relapse, and substance abuse in general. This study assessed recovered heroin and cocaine individuals in order to identify some of the factors that account for their ability to remain drug-free. Individual semi-structured interviews were conducted with the participants, each of whom had remained abstinent from their drug of choice for at least 10 months. These interviews were audio recorded and transcribed, and then analysed for themes using thematic content analysis. Findings of the study included the manner in which the recovered individual’s sense of agency vacillated between external and internal modes of attribution for their recovery and that systemic support was perceived as critical to continued abstinence. These findings imply that treatment providers consider both the risk for and protective factors against relapse as part of integrated systems in planning interventions.